A Vintage Wedding - Fforde, Katie (London Arrow Books, 2016)
In a small Cotswold country town, Beth, Lindy and Rachel are looking for new beginnings. So they set up in business, organising stylish and perfectly affordable vintage weddings. Soon they are busy arranging other people's Big Days. What none of them know is that their own romances lie waiting, just around the corner
Keywords: Weddings -- England -- England--Cotswold Hills